Cyclical Fluctuations in Brazil's Real Exchange Rate : The Role of Domestic and External Factors - Hoffmaister, Willy (IMF Working Papers; Working Paper, 1997)
This paper examines the effects of capital inflows and domestic factors on Brazil's real exchange rate. It describes the analytical framework, and then estimates a near-VAR model linking capital flows, interest rate differentials, government spending, money-base velocity, and the temporary component of the real exchange rate (TCRER). Generalized variance decompositions indicate that world interest rate shocks largely explain medium-term fluctuations in capital flows and the TCRER. Generalized impulse response functions show that a reduction in the world interest rate (and, to a lesser extent, an increase in government spending) have significant effects on the TCRER and capital flows.